2
$\begingroup$

Let $\dfrac{\tan A}{1-\tan^2A}=\sin^220^\circ-\sin160^\circ\sin220^\circ+\sin^2320^\circ$, find $\tan6A$

My attempt : \begin{align*} \dfrac{\tan2A}{2}=\sin^220^\circ-\sin20^\circ\sin40^\circ+\sin^240^\circ\\ \tan2A=2(\sin^220^\circ-\sin20^\circ\sin40^\circ+\sin^240^\circ) \end{align*} and \begin{align*} \tan6A&=\tan(2A-60^\circ)\tan2A\tan(2A+60^\circ)\\ &=(\dfrac{\tan2A-\sqrt{3}}{1+\sqrt{3}\tan60^\circ})(\tan2A)(\dfrac{\tan2A+\sqrt{3}}{1-\sqrt{3}\tan60^\circ}) \end{align*} give $$\tan6A=(\dfrac{2(\sin^220^\circ-\sin20^\circ\sin40^\circ+\sin^240^\circ)-\sqrt{3}}{1+\sqrt{3}\tan60^\circ})(2(\sin^220^\circ-\sin20^\circ\sin40^\circ+\sin^240^\circ))(\dfrac{2(\sin^220^\circ-\sin20^\circ\sin40^\circ+\sin^240^\circ)+\sqrt{3}}{1-\sqrt{3}\tan60^\circ})$$ This method is incredibly long, there may be better way to deal with this problem.

$\endgroup$
5
  • 2
    $\begingroup$ Hint: simplify first before you plug in the values. You should get $\sin^2 20^\circ-\sin160^\circ\sin220^\circ+\sin^2 320^\circ=\frac34$. $\endgroup$ – user10354138 Aug 8 '20 at 3:59
  • $\begingroup$ @user10354138 I came to $\sin^220^\circ(1+2\cos20^\circ+4\cos^220^\circ)$. Can you please hint more? $\endgroup$ – Ken Aug 8 '20 at 6:16
  • $\begingroup$ You have $\sin^2\theta(1+2\cos\theta+4\cos^2\theta)=\frac12(2+\cos\theta-\cos 2\theta-\cos 3\theta-\cos 4\theta)$. Now note that you have $\cos40^\circ+\cos80^\circ=2\cos60^\circ\cos20^\circ=\cos20^\circ$. $\endgroup$ – user10354138 Aug 8 '20 at 6:28
  • 1
    $\begingroup$ @user10354138 You should make that an answer. $\endgroup$ – Toby Mak Aug 8 '20 at 6:29
  • 2
    $\begingroup$ @TobyMak I was going to, then AsdrubalBeltran posted the exact simplication steps I used. $\endgroup$ – user10354138 Aug 8 '20 at 6:34
3
$\begingroup$

Note that: \begin{array}{} \dfrac{\tan2A}{2}&=&\sin^2160^\circ-\sin160^\circ\sin220^\circ+\sin^2220^\circ\\ \dfrac{\tan2A}{2}&=&(\sin160^\circ-\sin220^\circ)^2+\sin160^\circ\sin220^\circ\\ \dfrac{\tan2A}{2}&=&(\sin20^\circ+\sin40^\circ)^2-\sin20^\circ\sin40^\circ\end{array} Apply product-sum and sum-product \begin{array}{}\dfrac{\tan2A}{2}&=&(2\sin30^\circ\cos10^\circ)^2-\dfrac{\cos20^\circ-\cos60^\circ}{2}\\ \dfrac{\tan2A}{2}&=&\cos^210^\circ-\dfrac{1-2\sin^210^\circ}{2}+\dfrac{1}{4}\\ \dfrac{\tan2A}{2}&=&\cos^210^\circ+\sin^210^\circ-\dfrac{1}{4}\\ \dfrac{\tan2A}{2}&=&\dfrac{3}{4}\\ \tan(2A)&=&\dfrac{3}{2} \end{array}

$\endgroup$
1
  • 1
    $\begingroup$ Excellent answer ! $\endgroup$ – sai-kartik Aug 8 '20 at 6:29
1
$\begingroup$

Let me post a different route to the simplication, as OP has begun.

So we have $$ \sin^2 20^\circ-\sin160^\circ\sin220^\circ+\sin^2 320^\circ= \sin^2 20^\circ(1+2\cos 20^\circ + 4\cos^2 20^\circ) $$ I claimed for all $\theta$, $$ \sin^2\theta(1+2\cos\theta+4\cos^2\theta)=\frac12(2+\cos\theta-\cos2\theta-\cos3\theta-\cos4\theta) $$ Proof of claim: \begin{align*} LHS&=\sin^2\theta(1+2\cos\theta+4\cos^2\theta)\\ &=\frac12(1-\cos 2\theta)(3+2\cos\theta+2\cos2\theta)\\ &=\frac12(3+2\cos\theta-\cos2\theta-2\cos\theta\cos2\theta- 2\cos^22\theta)\\ &=\frac12(2+2\cos\theta-\cos2\theta-2\cos\theta\cos2\theta- \cos4\theta)\\ &=\frac12(2+\cos\theta-\cos2\theta-(4\cos^3\theta-3\cos\theta)- \cos4\theta)\\ &=\frac12(2+\cos\theta-\cos2\theta-\cos3\theta- \cos4\theta)\\ &=RHS\quad\checkmark \end{align*}

So with $\theta=20^\circ$, this is \begin{align*} &\sin^2 20^\circ(1+2\cos 20^\circ + 4\cos 40^\circ)\\ &=\frac12(2+\cos 20^\circ-\cos40^\circ-\cos60^\circ- \cos80^\circ)\\ &=\frac12\left(\frac32+\cos 20^\circ-\cos40^\circ-\cos80^\circ\right)\\ &=\frac12\left(\frac32+\cos 20^\circ-2\cos60^\circ\cos20^\circ\right)\\ &=\frac34. \end{align*} So $\tan 2A=\frac32$ and $$ \tan 6A=\tan 3(2A)=\frac{3\tan 2A-\tan^3 2A}{1-3\tan^2 2A}=\dots $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.